Uniwersytet Zielonogórski na rynku edukacyjnym. Analiza wyników rekrutacji na Wydział Pedagogiczny w latach 2002/03-2010/11 = University of Zielona Góra on the education market. The analysis of Education Faculty recruitment in the years 2002/2003-2010/2011 - Mianowska, Edyta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the analysis of dynamics of the number of candidates to the Education Faculty at the University of Zielona Gora in the years 2002/2003-2010/2011. The objective of the research was to trace the changes taking place in this field in the light of the transformations of higher education in Poland. Moreover, the author sought to characterize the selected features of candidates over the analyzed period. Thus the cognitive aim was to identify possible trends appearing in the outlined areas and to create a profile of a candidate.
Keywords: Uniwersytet Zielonogórski; Uniwersytet Zielonogórski - Wydział Pedagogiki, Socjologii i Nauk o Zdrowiu; rekrutacja